Biomarking Study of Aromatic Hydrocarbon Fraction Crude Oil Tarakan, North Kalimantan - Rafwan Year Perry Burhan; Abduh Muharram Chairacita; Yulfi Zetra; Endah Mutiara (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
The study of the aromatics of aromatic hydrocarbons from Tarakan crude oil, North Kalimantan, has been carried out through the analysis of Gas Chromatography-Mass Spectroscopy (GC-MS) analysis. The biomarkers identified showed the presence of naphthalene groups, phenanthrene and pentacyclic triterpenoids where the pentacyclic triterpenoid showed the highest abundance. The presence of 3,3,7-trimethyl-1,2,3,4-tetrahydrochrysene biomarkers; 1,2,9-trimethyl-1,2,3,4-tetrahydropicene; 2,7-dimethyl-1,2- (isopropylpenteno) -1,2,3,4-tetrahydrochrysene and dinorursa-1,3,5 (10), 13 (18) -tetraene as indicators of plants Angiosperms and chrysene indicate input bacteria. The existence of 1,3,7 + 2,6,9 + 2,7,9-TMP biomarkers; 3-MC and 2-MC indicate mature oil samples. The presence of DMP, TMP and chrysene biomarkers indicates terrestrial and marine depositional environments.